Design of a Computationally Efficient Dynamic System-Level Simulator for Enterprise LTE Femtocell Scenarios. (18th December 2012) - Ruiz-Avilés, J. M.; Luna-Ramírez, S.; Toril, M.; Ruiz, F.; de la Bandera, I.; Muñoz, P.; Barco, R.; Lázaro, P.; Buenestado, V.
Abstract : In the context of Long-Term Evolution (LTE), the next generation mobile telecommunication network, femtocells are low-power base stations that efficiently provide coverage and capacity indoors. This paper presents a computationally efficient dynamic system-level LTE simulator for enterprise femtocell scenarios. The simulator includes specific mobility and traffic and propagation models for indoor environments. A physical layer abstraction is performed to predict link-layer performance with low computational cost. At link layer, two important functions are included to increase network capacity: Link Adaptation and Dynamic Scheduling. At network layer, other Radio Resource Management functionalities, such as Admission Control and Mobility Management, are also included. The resulting tool can be used to test and validate optimization algorithms in the context of Self-Organizing Networks (SON).